Pharmacological cognitive enhancement in pediatrics. Issue 3 (June 2018) - Colaneri, Natalie; Sheldon, Mark; Adesman, Andrew
Abstract : Purpose of review: Given the pervasiveness of psychotropic medication in the youth population and an increasingly competitive culture regarding educational performance, children, teenagers, and/or their parents may increasingly seek psychotropic substances in an effort to enhance a student's cognitive abilities and/or academic performance. Physicians must become aware of this very important and clinically relevant issue and work to ensure that medications remain in the hands of patients seeking wellness and not enhancement. Recent findings: The current article highlights findings on the pervasiveness of stimulant misuse and diversion in youth, the motivations and effects of stimulant use, health and legal consequences associated with use, and physician perceptions and preventive practices. Ethical concerns regarding pharmacological cognitive enhancement in pediatrics are also outlined – including coercion for nonusers, inequities in access, and threats to an individual's sense of self with regard to authenticity and autonomy. Summary: Pharmacological cognitive enhancement in pediatrics will become a larger, clinically relevant issue in the coming years. Physicians who care for children and adolescents must become more aware of this issue. Given the myriad health, legal, and ethical concerns, clinicians should discourage use of pharmaceuticals for enhancement purposes in the pediatric population.